Изучение биоразнообразия PYRICULARIA ORYZAE CAV. в рисосеющих зонах юга России на основе методов ПЦР - E. V. Dubina; P. I. Kostylev; M. G. Ruban; Yu. V. Aniskina; I. A. Shilov; N. S. Velishaeva; L. V. Esaulova (Зерновое хозяйство России)
The study of biodiversity of Pyricularia oryzae Cav. in the rice-growing areas of the south of Russia using the methods of PCR On the basis of molecular-genetic approaches there has been conducted the study of biodiversity of phyto pathogenic fungus Pyricularia oryzae Cav. in the south of Russia. We have conducted the monitoring and selected the isolates of the pathogen from the infected herbarium material, collected from the fields of six rice-growing areas of the Krasnodar Kray with various degree of harmfulness of rice blast pathogen. Their DNA-passports have been made. The studied isolates of the blast pathogen have been characterized in respect of their morphological traits. The phyto-pathological test with the application of varieties-differentiators of rice has established quantitative and qualitative composition of the virulent genes in fungus strains. The study has found the genes of pathogen tolerance, greatly efficient in the south of Russia, which can be recommended for the breeding programs for growing rice varieties resistant to rice blast.